Tobacco Use Among Siblings of Childhood Cancer Survivors: A Report From the Childhood Cancer Survivor Study. Issue 2 (25th August 2015) - Buchbinder, David; Oeffinger, Kevin; Franco‐Villalobos, Conrado; Yasui, Yutaka; Alderfer, Melissa A.; Armstrong, Gregory T.; Casillas, Jacqueline; Ford, Jennifer; Krull, Kevin R.; Leisenring, Wendy; Recklitis, Christopher; Robison, Leslie L.; et al.
Abstract : Background: Having a brother or sister with childhood cancer may influence health behaviors during adulthood. The aim of this study was to compare tobacco use in siblings of survivors with peers and to identify factors associated with sibling tobacco use. Procedures: A retrospective cohort study was conducted using adult siblings (N = 1, 974) of 5+ year cancer survivors in the Childhood Cancer Survivor Study (CCSS) and participants (N = 24, 105, weighted to match CCSS) in the 2007 National Health Interview Survey. Self‐reported tobacco use, sociodemographic, and cancer‐related risk factors were analyzed. Results: Siblings were equally likely to have ever smoked compared to their peers (odds ratio [OR] 1.02, 95% confidence interval [CI] 0.93–1.12). Siblings were less likely to be current smokers (OR 0.83, 95%CI 0.73–0.94), but more likely to be former smokers (OR 1.21, 95%CI 1.08–1.35). Siblings with low education were more likely to ever smoke (OR 1.51, 95%CI 1.15–2.00) and be current smokers (OR 1.67, 95%CI 1.24–2.26) compared to their peers. Among siblings, risk factors for current tobacco use included the following: low income <20, 000 (OR 1.66, 95%CI 1.09–2.54), low education (OR 6.68, 95%CI 4.07–10.97), psychological distress (OR 5.36, 95%CI 2.21–13.02), and heavy alcohol use (OR 3.68, 95%CI 2.50–5.41). Conclusions: Siblings of survivors take up smoking at similar rates to their peers, but are more likely to quit. Efforts are needed to address disparities by providing greater psychosocial support and education for the lowest socioeconomic status families facing childhood cancer. Pediatr Blood Cancer 2015; 9999:XX–XX © 2015 Wiley Periodicals, Inc.